2019
DOI: 10.3390/atoms7010012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Runaway Electron Current Estimation in COMPASS Tokamak

Abstract: Runaway electrons present a potential threat to the safe operation of future nuclear fusion large facilities based on the tokamak principle (e.g., ITER). The article presents an implementation of runaway electron current estimations at COMPASS tokamak. The method uses a theoretical method developed by Fujita et al., with the difference in using experimental measurements from EFIT and Thomson scattering. The procedure was explained on the COMPASS discharge number 7298, which has a significant runaway electron p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Runaway electrons are a fundamental physical phenomenon in natural [1][2][3][4][5][6] and laboratory discharges [7][8][9][10][11][12][13][14], including sparks over meter gaps [15][16][17][18], and in systems for controlled thermonuclear fusion [19][20][21]. The fact that runaway electrons do exist in discharges in the upper atmosphere was predicted by С.Т.R.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Runaway electrons are a fundamental physical phenomenon in natural [1][2][3][4][5][6] and laboratory discharges [7][8][9][10][11][12][13][14], including sparks over meter gaps [15][16][17][18], and in systems for controlled thermonuclear fusion [19][20][21]. The fact that runaway electrons do exist in discharges in the upper atmosphere was predicted by С.Т.R.…”
Section: Introductionmentioning
confidence: 99%
“…Some data on these studies can be found elsewhere [51][52][53]. By now, thousands of research papers are available on runaway electrons and x rays in different conditions, including those at low pressures and voltages [51][52][53], in meter gaps [15][16][17][18] and shorter [54][55][56][57][58], in different atmospheric discharges [2][3][4][5][6], and in systems for controlled thermonuclear fusion like Tokamak [19][20][21]. Providing a complete coverage of all in one review is impossible, and so we focus only on those data which allow the reader to understand the role of runaway electrons in gas discharges in an inhomogeneous electric field at a pressure of 0.01-1.2 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and modelling efforts contributed significantly to the understanding of crucial topics, such as alternative or more efficient mitigation methods [35][36][37] or even termination of the RE beam [38]. The physics of RE interaction with mitigation species and materials, loss mechanisms, transport, interaction with naturally present or artificially created magnetic perturbations, and the RE impact on plasma-facing components was addressed in recent dedicated experimental campaigns in COMPASS [39][40][41]. The improved knowledge of RE behaviour was applied in the worldwide unique RE radial feedback control algorithm [42] and advanced beam detection with an extended set of dedicated diagnostic systems [43][44][45].…”
Section: Run-away Electrons (Res) Physicsmentioning
confidence: 99%
“…A more suitable approach to the RE beam feedback is to use relativistic pressure. This was applied in the calculation of RE current fraction in thermal plasma in [37] and more recently in [38]. In this case, it is suitable to use the relativistic pressure formula given by the equation [37]…”
Section: Mhd Equilibrium Approximation For the Re Beammentioning
confidence: 99%